Pemberian Insentif Dengan Peningkatan Motivasi Kerja Perawat Di Instalasi Rawat Inap RSUD M. Sani - Sri Muharni; Utari Christya Wardhani; Muhamad Zulhan (Journal of Health (JoH), 2020)
Motivation with an encouraging or retrospective compensation that is regarded as what makes them work better. The purpose of this research is to know the relationship of giving incentives to the motivation work of nurses in the inpatient installation of RSUD M. SANI. This research draft is quantitative with sampling methods using Total Sampling. The samples in this study consisted of 86 nurses and data analyzed using the Spearman Rank analysis test. The results of the study showed that the number of respondents who were less incentive and good had a comparison of 43 respondents (50%). The most number of respondents has a good work motivation of 50 (58,1%). There is an incentive-granting relationship with the work motivation of nurses working in the inpatient installation of RSUD M. Sani with two variables in the Medium category (p value = 0,000, Rho = 0,424). In this case the hospital is expected to be able to pay attention and increase incentives. The feasible and reasonable thing is to make clear target work conditions so that the wishes of work can increase.